Public Debt, Economic Growth and Fiscal Balance: Alternative Measures of Sustainability in the Indian Context. Issue 3 (June 2020) - Sasmal, Joydeb; Sasmal, Ritwik
This article has examined the impact of public expenditure on economic growth and viability of fiscal policy when the deficit in budget is financed by public borrowing. A number of alternative criteria have been used as indicators of solvency in fiscal balance. The study is based on the theoretical framework and supported by the results of time series analysis in the Indian context. It is found that the share of revenue expenditure (RE) of the government has significantly increased over time and many of the components of RE are non-developmental in nature. The article argues that if growth suffers, it will put adverse impact on fiscal balance. The ratio of gross fiscal deficit (GFD) to net national product (NNP) and growth of NNP are co-integrated, and the ratio is found to increase with increase in NNP indicating deterioration in fiscal balance. The increase in total expenditure of the government has caused rise of the ratio of revenue deficit to total spending. Interest payment on public debt has led to the increase of the ratio of GFD to income. These results are indicators of non-viability of fiscal policy in India at least in the short run.